Biomass-based aligned carbon networks with double-layer construction for tunable electromagnetic shielding with ultra-low reflectivity. (20th March 2022) - Chen, Jiali; Yi, Da; Jia, Xichen; Wang, Guoqing; Sun, Zhouping; Zhang, Lihua; Liu, Yinfeng; Shen, Bin; Zheng, Wenge
Highlights: The EMI SE of aligned carbon networks can be accurately controlled by changing the cross-angle. The construction of Salisbury absorber-liked double-layer structure can result in an ultra-low EM reflection but enhanced SE variation range. It provides a simple and effective way for constructing high-performance biomass carbon materials with adjustable EMI shielding and ultra-low reflectivity. Abstract: Nowadays, carbon frameworks derived from natural biomaterials have attracted extensive attention for electromagnetic interference (EMI) shielding due to their renewability and affordability. However, it is critical and challenging to achieve effective regulation of shielding effectiveness (SE) as well as weaken the strong EM reflection of highly conductive biomass-based carbon materials. Herein, commercial cotton pads with oriented structure were selected as carbonaceous precursor to fabricate aligned carbon networks by pyrolysis, and the EMI SE of the samples with increased temperature of 800-1000 °C can be accurately controlled in the effective range of ∼21.7-29.1, ∼27.7-37.1 and ∼32.7-43.3 dB with high reflection coefficient of >0.8 by changing the cross-angle between the electric-field direction of incident EM waves and the fiber-orientation direction due to the occurrence of opposite internal electric field. Moreover, the further construction of Salisbury absorber-liked double-layer structure could result in an ultra-low reflection coefficient of only ∼0.06 but enhanced SE variation range up to ∼38.7-49.3 dB during the adjustment of cross-angle, possibly due to the destructive interference of EM waves in the double-layer carbon networks. This work would provide a simple and effective way for constructing high-performance biomass carbon materials with adjustable EMI shielding and ultra-low reflectivity. Graphical Abstract: Image, graphical abstract